ServiceNow: Boosting Productivity and Innovation in Healthcare, Manufacturing, and Research - Kamala Kannan Munusamy Ethirajan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
ServiceNow has emerged as a transformative force in enterprise digital transformation across healthcare, manufacturing, and research sectors. The platform's multi-instance cloud architecture enables robust workflow automation and system integration capabilities, fundamentally changing how organizations operate and deliver services. In healthcare, ServiceNow optimizes patient care through automated scheduling, EHR integration, and clinical pathway management, while ensuring regulatory compliance. The manufacturing sector benefits from enhanced production workflows, quality control automation, and predictive maintenance through IoT integration and real-time analytics. In research institutions, the platform streamlines grant management, resource allocation, and regulatory compliance while enabling secure collaboration across organizations. The implementation of comprehensive security measures, including end-to-end encryption and multi-factor authentication, ensures data protection across all sectors. Through phased implementation approaches and continuous improvement processes, organizations achieve significant operational efficiencies and cost reductions. Future developments in AI/ML integration and advanced connectivity options promise to further enhance the platform's capabilities in process automation and decision support.
Keywords: Digital Transformation; Enterprise Automation; Cloud Infrastructure; Workflow Optimization; Cross-sector Integration